Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Thelma Joy Fromm, December 20, 1986 - Fromm, Thelma Joyet al (1986)
Iowa Christmas bird counts of regular and uncommon species found in Mason City contributed by Thelma Joy Fromm, December 20, 1986. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1986-1987. Epson - sheet feed